Development and Effectiveness of an Interactive Prompt Engineering E-Module to Enhance Vocational Students’ Learning Outcomes - Aditya Arya Sukma; Rizki Hikmawan (Journal of Educational Sciences, 2026)
This study aimed to develop and evaluate an interactive e-module on Prompt Engineering to support the use of generative AI in learning for vocational students. The research employed a 4-D (Define, Design, Develop, Disseminate) Research and Development model and a one-group pretest–posttest design, the study involved 113 students in self-directed learning. Data were analyzed using the Wilcoxon Signed-Rank test. Results indicated a significant difference between pretest and posttest scores (pretest: M = 67.52, SD = 6.09; posttest: M = 81.06, SD = 5.41; ΔM = 13.54) (p < 0.001) with a large effect size (r = 0.85), indicating that the e-module effectively enhanced conceptual understanding, prompt-writing skills, and AI ethics. The effectiveness was supported by multimedia integration, project-based activities, and the Prompt RACE approach fostering reflective and contextual learning. The study contributes to strengthening AI literacy in vocational education and provides an adaptive e-module model applicable across vocational disciplines.